Mapping the aberrant brain functional connectivity in new daily persistent headache: a resting-state functional magnetic resonance imaging study - Wei Wang; Ziyu Yuan; Xueyan Zhang; Xiaoyan Bai; Hefei Tang; Yanliang Mei; Dong Qiu; Yingkui Zhang; Peng Zhang; Xue Zhang; Yaqing Zhang; Xueying Yu; et al. (The Journal of Headache and Pain, 2023)
Abstract Background and purpose The pathogenesis of new daily persistent headache (NDPH) is not fully understood. We aim to map aberrant functional connectivity (FC) in patients with NDPH using resting-state functional magnetic resonance imaging (MRI). Methods Brain structural and functional MRI data were acquired from 29 patients with NDPH and 37 well-matched healthy controls (HCs) in this cross-sectional study. Region of interest (ROI) based analysis was used to compare FC between patients and HCs, with 116 brain regions in the automated anatomical labeling (AAL) atlas were defined as seeds. The correlations between aberrant FC and patients’ clinical characteristics, and neuropsychological evaluation were also investigated. Results Compared with HCs, patients with NDPH showed increased FC in the left inferior occipital gyrus, right thalamus and decreased FC in right lingual gyrus, left superior occipital gyrus, right middle occipital gyrus, left inferior occipital gyrus, right inferior occipital gyrus, right fusiform gyrus, left postcentral gyrus, right postcentral gyrus, right thalamus and right superior temporal gyrus. There were no correlation between FC of these brain regions and clinical characteristics, neuropsychological evaluation after Bonferroni correction (p > 0.05/266). Conclusions Patients with NDPH showed aberrant FC in multiple brain regions involved in perception and regulation of emotion and pain. Trial registration ClinicalTrials.gov Identifier: NCT05334927.